PENAMBAHAN LATIHAN NEURAC TERHADAP RESISTANCE TUBE EXERCISE TIDAK LEBIH MENINGKATKAN KETEPATAN TENDANGAN PADA PEMAIN SEPAK BOLA - Manik, James W H; Adiatmika, I Putu; Irfan, Muh.; Adiputra, Luh Made Indah Sri Handari; Griadhi, I Putu Adiartha; Lesmana, S. Indra (Sport and Fitness Journal, 2017)
Background: One of the things that greatly affect the capability and performance of lower trunk and lower extremity is core stability. Core stability is the ability to control the position and movement of the trunk to pelvic used to produce, transfer and control the power and motion to with the final segment of the integrated activities. Method: The study was a randomized experimental design with pre- and post-test control group design. 34 students from SMU Olahraga Ragunan Jakarta students between 16-19 years old which is participating as sample on 6 weeks research on Mei-June 2016. The group was divided into two groups-first group doing tube resistance exercise and second group doing combination of tube resistance exercise and neurac training. Measurement instruments used were kicking the ball into the goal using the method of measurement by Finnoff. Measurements were taken before treatment and after treatment. Result: The mean accuracy of the first group before treatment 9.882 ± 2.11, after treatment 11.058 ± 1:51 after tested with paired samples t-test has increased significantly (p = 0.03). The mean accuracy kick second group before treatment 10,588±3,624, after treatment 12,470±3,184, after being tested with paired samples t-test experienced a significant improvement (p = 0.002). The mean difference in accuracy kick of first group (9.882 ± 2.11) compared with second group (11.058 ± 1:51) tested by Mann Whitney U test has no significant difference p = 0.495 (p?0.05). Conclusion: The conclusions of this research is Replenishment of Neurac Exercise to Resistance Tube Exercise Not Increasing Kicking Accuration on Soccer Player of SMUN Olahraga Ragunan Jakarta Student